Relationship between Critical Thinking Skills and Creative Thinking Skills with the Biology Learning Outcomes of Grade XI Students at UPT SMAN 1 Wajo - Yanti, Hasvika; Andi Badli Rompegading; Muhammad Nasir (Bioeduca : Journal of Biology Education, 2025)
This study aims to determine the relationship between critical thinking skills and creative thinking skills with the biology learning outcomes of grade XI students at UPT SMAN 1 Wajo.  This study is based on the demands of 21st century learning, which emphasizes the development of higher-order thinking skills, such as critical and creative thinking, in biology lessons. This study used a descriptive-quantitative method. The research population consisted of 11th grade students at UPT SMAN 1 Wajo, and the sample was taken using purposive sampling of 31 students. The results showed a positive and significant relationship between critical thinking skills and creative thinking skills with students' biology learning outcomes, with a significance value of 0.000 < 0.05 and a correlation coefficient value of 0.972, which is classified as a very strong correlation. This study concluded that simultaneously, higher critical thinking skills and creative thinking skills play an important role in improving students' biology learning outcomes.